Tax Review Aspek Perpajakan atas Pengalihan Hak Tanah dan Bangunan dengan mekanisme Perjanjian Nominee - Muhammad Taufiq Budiarto (Jurnal Pajak dan Bisnis, 2021)
Nowdays, many companies and non residents who want to invest in Indonesia. One of business capitals which foreign investors should have is a land. The principle of Indonesian agrarian law is nationallity, which means only Indonesian have right to own of the land. The existing agrarians law make the foreigner fall into a nomine agreement have a right to have a land. The method which is used in this paper is normative juridical which examines the normative aspects of legislation, especially the provisions on taxation and the Basic Agrarian Law Act. This paper will illustrate investment practices through nominee agreements. The purpose of this paper is to discuss whether the practice of nominee agreements is indicative of tax avoidance or tax evasion . It has fulfilled the meaning of criminal acts in the field of taxation which is known from its criminal elements in the form element of subject – elemen of actions, elemen of Effects and elemen of Errors. One of the issues which is discussed in this paper is the act of buying land in the tourist areas, specifically in Bali and Lombok. There are a lot of numbers in schemes which are occurred. It will be known as the actual Beneficial Owner income recipient, and also the tax aspects which must be collected from the scheme.